Usefulness of Modified Alvarado Score in Diagnosis of Acute Appendicitis in Adults (Bangladesh Journal of Medical Science, 2015)
Background: Definitive diagnosis of acute appendicitis preoperatively is sometimes difficult. Failure to make a diagnosis is the main reason for persistent rate of morbidity and mortality. Various scoring systems are devised to aid diagnosis of acute appendicitis. In some studies the modified Alvarado score was helpful, reliable and practical in minimizing unnecessary appendectomy. Objective: The purpose of this study was to evaluate the usefulness of modified Alvarado score for the diagnosis of acute appendicitis. Materials and Method: A prospective study of 89 adult patients, admitted with abdominal pain suggestive of acute appendicitis, from July 2011 to June 2012, was conducted. Data including clinical signs and symptoms and laboratory findings were recorded in modified Alvarado score record form. All 89 patients underwent appendectomy. Final diagnosis was confirmed by histopathological examination. Reliability of scoring system was assessed by negative appendectomy rate and positive predictive value. Results: Out of 89 patients who underwent appendectomy, 85 had acute appendicitis on histopathology. Positive predictive value was 95.5% and negative appendectomy rate was 4.5%. 52.8% had score 7 or above and 47.2% had score less than 7. From score it is difficult to predict which patient warranted appendectomy and who may be safely observed or discharged. Conclusions: Diagnosis of acute appendicitis remains mainly clinical evaluation and it is more helpful than modified Alvarado scoring system in adults.Bangladesh Journal of Medical Science Vol.14(4) 2015 p.336-338